DO ACCOUNTABILITY, POPULATION QUALITY, ORGANIZATIONAL SIZE, ECONOMIC GROWTH AND COVID-19, AFFECT REGIONAL INDEPENDENCE - Priharjanto, Akhmad; Andriana, Nina; Hadiwibowo, Yuniarto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study is a quantitative study to test whether accountability, population quality, organizational size, economic growth, and covid-19, affect regional independence. The study was conducted for the scope in Java. The data used in this study are secondary data obtained through the Central Statistics Agency. Data was taken from the Central Statistics Agency for the period 2013 to 2021. Data analysis used multiple linear regression with the STATA application. The results of the statistical test show that the accountability variable (opinion) p-value is 0.001, which means that accountability significantly affects regional independence, as well as the population quality variable indicated by the HDI. The p-value for the HDI is 0.000 which can be said that the HDI significantly affects regional independence. The same results are also shown by the variable organizational size (SIZE) which indicated by the assets owned by the regional government (ASETKAP), the p-value of the size of the regional government is 0.000. This means that the size of the government significantly affects regional independence. The variables COVID-19 (COVID) and economic growth (ADHBKAP) also have a significant positive influence.